La démesure et l’indocilité du vivant. Intermittences de la botanique dans deux romans du cycle des Rougon-Macquart de Zola - Rachwalska von Rejchwald, Jolanta (Studia Romanica Posnaniensia, 2025)
Even though the nineteenth century saw the significant development of botany, Émile Zola, an enthusiast of progress and the modern city, made it part of his cycle sparingly, making it a botanical counterpoint that punctuates subtly his work. There are four novels in the Rougon-Macquart cycle where the plant appears in the form of sequences that develop a kind of plant cosmopoetics: La Fortune des Rougon, La Curée, Le Ventre de Paris and La Faute de l’abbé Mouret. We have chosen two of them (La Fortune des Rougon and Le Ventre de Paris to demonstrate that with each appearance, the plant in the form of ruderal plants or vines becomes a powerful narrative spring that establishes, at the same time, a novelistic topo-energetic and a symbolic device. There are two possible readings of these botanical sequences: one that is integrated into the novelistic ecosystem specific to each of these four novels and the other that shows how they function from the perspective of the whole.